1996
DOI: 10.1111/1523-1747.ep12338472
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Tyrosine Phosphatases Expressed in Mouse Epidermal Keratinocytes

Abstract: The importance of growth factors acting via receptor-type protein-tyrosine kinases in the continuous renewal of the epidermis from the keratinocyte stem cell population has been well established. Protein-tyrosine phosphatases (PTPases), which dephosphorylate phosphotyrosine-containing proteins, may therefore be expected to play an equally important role in the control of epidermal growth and differentiation. In this study, we have made an inventory of the various PTPases that are expressed during mouse keratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…data]. Both of these PTPs are known to be expressed in mouse epidermal keratinocytes [Hendriks et al, 1996] and normal human skin [Nanney et al, 1997]. In HaCaT cells, the localization of PTP1B was confined to the perinuclear cytoplasm (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…data]. Both of these PTPs are known to be expressed in mouse epidermal keratinocytes [Hendriks et al, 1996] and normal human skin [Nanney et al, 1997]. In HaCaT cells, the localization of PTP1B was confined to the perinuclear cytoplasm (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The maturation includes the formation of a cornified envelope, the loss of the nucleus, the elimination of the plasma membrane and keratinisation [2]. The cell transformations occurring during the differentiation of the keratinocytes are activated and controlled by kinases and phosphatases [3]. In fact, these enzymes are part of a group that not only performs a kinase regulation function but which is also involved in other functions, in particular, the transformation of profilaggrins into filaggrins, enhancing the association of keratins to form macrofilaments in the stratum granulosum [4].…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies of PTPs in skin showed that despite the fact that PTP expression is induced during keratinocyte proliferation and maturation, their expression levels remain unchanged within epidermal tissue14. Exposure to acute ultraviolet (UV) irradiation or treatment with the tumor promoter, 12- O -tetradecanoylphorbol-13-acetate (TPA), increases the activation of PTKs including the epidermal growth factor receptor (EGFR) and the downstream STAT3 signaling pathway151617181920.…”
mentioning
confidence: 99%